Macrophage migration inhibitory factor receptor CD74 expression is associated with expansion and differentiation of effector T cells in COVID-19 patients - Westmeier, Jaana; Brochtrup, Annika; Paniskaki, Krystallenia; Karakoese, Zehra; Werner, Tanja; Sutter, Kathrin; Dolff, Sebastian; Limmer, Andreas; Mittermüller, Daniela; Liu, Jia; Zheng, Xin; Koval, Tetiana; et al. (Frontiers in Immunology, 2023)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) caused millions of COVID-19 cases and deaths worldwide. Severity of pulmonary pathologies and poor prognosis were reported to be associated with the activation non-virus-specific bystander T cells. In addition, high concentrations of the macrophage migration inhibitory factor (MIF) were found in serum of COVID-19 patients. We hypothesized that these two pathogenic factors might be related and analyzed the expression of receptors for MIF on T cells in COVID-19. T cells from PBMCs of hospitalized patients with mild and severe COVID-19 were characterized. A significantly higher proportion of CD4+ and CD8+ T cells from COVID-19 patients expressed CD74 on the cell surface compared to healthy controls. To induce intracellular signaling upon MIF binding, CD74 forms complexes with CD44, CXCR2, or CXCR4. The vast majority of CD74+ T cells expressed CD44, whereas expression of CXCR2 and CXCR4 was low in controls but increased upon SARS-CoV-2 infection. Hence, T cells in COVID-19 patients express receptors that render them responsive to MIF. A detailed analysis of CD74+ T cell populations revealed that most of them had a central memory phenotype early in infection, while cells with an effector and effector memory phenotype arose later during infection. Furthermore, CD74+ T cells produced more cytotoxic molecules and proliferation markers. Our data provide new insights into the MIF receptor and co-receptor repertoire of bystander T cells in COVID-19 and uncovers a novel and potentially druggable aspect of the immunological footprint of SARS-CoV-2.